Sub-seasonal to seasonal drivers of dry extreme rainfall events over Northeast Thailand - Abatan, Abayomi A.; Collins, Matthew; Babel, Mukand S.; Khadka, Dibesh; De Silva, Yenushi K. (Frontiers in Climate, 2023)
The interannual El Niño-Southern Oscillation (ENSO) and the Boreal Summer Intraseasonal Oscillation (BSISO) strongly modulate sub-seasonal to seasonal rainfall variability, leading to dry extreme rainfall events (DEREs) over Northeast (NE) Thailand. In this study, the ability of climate models to simulate the ENSO-BSISO-induced DEREs and associated synoptic features are evaluated using self-organising maps. Observed DEREs occur most frequently during ENSO Neutral and La Niña conditions, when enhanced convection is located over central India and the Bay of Bengal. The intensity of observed DEREs are strengthened during El Niño when enhanced convection is observed over the western Pacific region. The climate models exhibit a diverse frequency of DEREs during ENSO phases, with some models showing better skill than others. On intraseasonal time scales, observed DEREs are favored when enhanced BSISO convection in phases 3 – 5 is located over the Bay of Bengal and the western Pacific region. 5 models out of the 19 examined capture the observed pattern during BSISO phases 4 and 5, while only 3 models capture the BSISO phase 3 behavior. Composite maps of observed DEREs during the combined BSISO and ENSO conditions indicate that BSISO convection increases (decreases) DERE frequency during El Niño and Neutral (La Niña) phase(s). Climate models can simulate the occurrence of dry events associated with the combined BSISO and ENSO phases, but they do so in different BSISO phases.